CULTURAL DIVERSITY AS A DRIVER FOR ENVIRONMENTAL ACTION - Mihaela Onofrei; Dana-Claudia Cojocaru; Sorin Gabriel Anton (Ekonomický Časopis)
Reducing greenhouse gas emissions is now a top priority on the global political agenda. In recent years, the European Union has adopted various policies to protect and enhance our ecosystem. However, policymakers should also take cultural values into account, as understanding cultural values can greatly influence how environmental policies are perceived and implemented locally. As there are few studies examining their impact on pollution abatement in the EU Member States, this paper attempts to fill this gap. Therefore, the objective of the paper is to investigate the relationship between cultural factors and greenhouse gas emissions at the level of the 27 EU member states for the period 1990-2019. Our results show that the role of cultural dimensions in reducing pollution in the EU member states can vary according to the specific cultural dimension measured according to Hofstede's methodology. In this context, the power distance index, masculinity, individualism, uncertainty avoidance index, and long-term orientation have a statistically significant and positive influence on the dependent variables used. Our study can be used as a starting point for researchers who want to deepen comprehensive analyses of individuals’ behaviour to reduce pollution or for policymakers to develop effective environmental policies.